FORUM MŁODYCHIsolated coronary artery bypass grafting in extracorporeal circulation in patients over 65 years old – does age still matter? - Miśkowiec, Dawid; Walczak, Andrzej; Ostrowski, Stanisław; Wrona, Ewa; Bartczak, Karol; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: Coronary artery bypass grafting (CABG) is conducted more and more commonly in patients in advanced age. Aim of the study : To analyze the influence of age and concurrent risk factors on the complications and early mortality after CABG. Material and methods: Medical records of 2194 patients were analyzed retrospectively. A group of 1303 patients who had undergone isolated CABG was selected. 106 (4.8%) patients were excluded due to missing data in their medical records. The remaining 1197 patients were divided into two subgroups by age: 1st group < 65 years (n = 662; 55.3%); 2nd group ≥ 65 years (n = 535; 44.7%). Results: The total 30-day mortality was 3.93% and was six times higher in the older group (1.21 vs. 7.29%; p < 0.001). Complications were observed in 176 (14.70%) patients, more often in the older group (10.42% vs. 20.0%; p < 0.001). In this group all kinds of complications were noted more often and in particular: postoperative myocardial infarction (1.96% vs. 5.42%; p = 0.001), respiratory dysfunction (1.36% vs. 4.11%; p = 0.005), neurological complications (1.81% vs. 3.74%; p = 0.04) and multi-organ dysfunction syndrome (0.30% vs. 1.68%, p = 0.03). The older patients required longer time under mechanical ventilation (24.0 ± 27.9 vs. 37.0 ± 74.1 hours; p = 0.004) and stayed longer in the intensive care unit: 2.5 ± 3.0 vs. 4.1 ± 7.84 days; p < 0.001. Independent predictors of death were: female sex [OR (95% CI) = 2.4 (1.2-4.5)], age ≥ 65 years [OR = 4.9 (2.1-11.1)], eGFR 72 minutes [OR = 5.5 (2.7-10.9)] and left main stem stenosis (> 50%) [OR = 2.4 (1.3-4.6)]. Conclusions: Age still significantly influences postoperative complications and mortality after isolated CABG.